STRATEGI DINAS KESEHATAN KOTA PEKANBARU DALAM PENCEGAHAN DEMAM BERDARAH DENGUE (DBD) DI KOTA PEKANBARU TAHUN 2021-2022 - Putri, Denisa Suwandi; ', Hasanuddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Dengue Hemorrhagic Fever, abbreviated as DHF, is an infectious disease caused by the dengue virus which is transmit by the Aedes aegypti mosquito. DHF is often found in tropical areas, one of which is Pekanbaru City. In 2021-2022, the number of dengue fever cases experienced a spike in Pekanbaru City.The aim of this research is to determine the strategy of the Pekanbaru City Health Service in preventing dengue hemorrhagic fever (DHF) in Pekanbaru City. The basis of the research used is a qualitative method with descriptive research type. The research location is the Pekanbaru City Health Service office. Data collection uses interview and documentation techniques. In this research, researchers used the theory put forward by Hadari Nawawi (2017) regarding the strategies of non-profit organizations in the government sector, namely aggressive strategies, conservative strategies and preventive strategies. The results of the research show that the Pekanbaru City Health Service has implemented a strategy to prevent dengue hemorrhagic fever (DHF), but it has not been optimal. In implementing the strategy, the Pekanbaru City Health Service created a dengue prevention strategy in accordance with the implementation of the Indonesian Ministry of Health's policy, the Puskesmas and Jumantik cadres became an extended hand in implementing the strategy, there was additional counseling in the waiting room and training on new programs from the Pekanbaru City Health Center, and the establishment of communication and good coordination from various parties. However, several shortcomings were still found in this research, such as uneven monitoring of mosquito nest eradication (PSN) to residents' homes from Community Health Centers and Jumantik Cadres, lack of health promotion in utilizing technology, limited budget in implementing the strategy, and the need for emphasis at the lowest level so that the strategy is optimal. Pekanbaru City Health Service in preventing dengue fever in Pekanbaru City. Keywords: Government Strategy, Prevention, Dengue Hemorrhagic Fever (DHF)